IDENTIFICATION OF STRENGTHS AND WEAKNESSES, OPPORTUNITIES AND THREATS FOR THE DEVELOPMENT OF BEEKEEPING IN BULGARIA - Haik Garabedian (Journal of Bio-Based Marketing, 2021)
Favorable natural and climatic conditions are one of the important factors for achieving competitiveness of the sector. Thanks to the influence of the Common Agricultural Policy in recent years, Bulgaria has become a leader in the production and export of honey as a member of the EU. This proves that the favorable natural and climatic conditions are only a prerequisite for successful development of the sector. In order to achieve lasting competitive advantages, it is necessary to implement an adequate policy to promote the development of the sector, identifying the main obstacles to the future development of the sector. The aim of the study is to identify the main obstacles to the sustainable development of beekeeping farms in Bulgaria through the SWOT application. It can be summarized that the future development of beekeeping farms cannot take place without the active financial support of the CAP. This support is necessary due to the fact that these farms are the backbone of rural economic development. Farmers have a strong motivation to develop their farms, which is determined by the desire to ensure a better way of life. In the present study, the realization of these opportunities is based on the strengths of beekeeping.